Emergence of stationary multimodality under two-timescaled dichotomic noise - Budini, Adrián Adolfo; McHardy, Isaias; Caceres, Manuel Osvaldo; Nizama, Marco (American Physical Society, 2020)
Fil: Budini, Adrián Adolfo Comisión Nacional de Energía Atómica, Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas, Argentina; Universidad Tecnológica Nacional, Argentina